Pengaruh Paparan Konten Cyber Victimization, dan Kontrol Sekolah terhadap Perilaku Cyberbullying pada Remaja SMA di Kota Depok - Dewi, Evie Ariadne Shinta; Aully, Marfa; Prihandini, Puji (Universitas Tribhuwana Tungga Dewi, 2025)
Cyberbullying is an act of violence on the internet that is still rampant, especially affecting students. Not only as victims, these students can also act as perpetrators. There are several factors that influence cyberbullying behavior, including the influence of content exposure, cyber victimization, and school control. This Quantitative study aims to analyze the influence of content exposure, cyber victimization, and school control on cyberbullying behavior in adolescents, especially high school students in Depok City. The hypothesis of this study is compiled based on the concept of cyberbullying factors proposed by Bae Sungman, into 3 hypotheses, namely, H1 Content exposure has an impact on cyberbullying behavior, H2 Cyber Victimization has an impact on cyberbullying behavior and H3 School Control has an impact on cyberbullying behavior. The results show that content exposure has an influence on cyberbullying behavior, where more exposure will increase the likelihood of someone committing cyberbullying. In addition, someone who has been a victim or exposed to cyber victimization will be more likely to become a perpetrator of cyberbullying. However, in this study, School Control has no influence on cyberbullying behavior among high school adolescents in Depok City, or H0 can be accepted and H3 is rejected. In this study, school control includes school regulations related to cyberbullying and regulations on the use of cellphones and social media at school. Some factors that make school control not influential include almost 50% of students not knowing that their school has regulations regarding cyberbullying and the use of social media. In addition, there is no supervision from teachers in the use of student social media, meaning that schools have not been optimal in enforcing these cyberbullying rules.Cyberbullying merupakan tindakan kekerasan di internet yang masih marak terjadi terutama menimpa para pelajar. Tidak hanya sebagai korban, para pelajar ini juga bisa bertindak sebagai pelaku. Terdapat beberapa faktor yang memengaruhi perilaku Cyberbullying, antara lainÂ pengaruh paparan konten, cyber victimization, dan kontrol sekolah. Penelitian kuantitatif ini ini bertujuan untuk menganalisis pengaruh paparan konten, cyber victimization, dan kontrol sekolah terhadap perilaku cyberbullying pada remaja, khususnya siswa SMA di Kota Depok. Hipotesis penelitian ini disusun berdasarkan konsep faktor cyberbullying yang dikemukakan oleh Bae Sungman, menjadi 3 hipotesis yaitu, H1 Paparan konten memiliki dampak terhadap perilaku cyberbullying, H2 Cyber Victimization memiliki dampak terhadap perilaku cyberbullying dan H3 Kontrol Sekolah memiliki dampak terhadap perilaku cyberbullying. Hasil riset menunjukkan paparan konten memiliki pengaruh terhadap perilaku cyberbullying, dimana semakin banyak paparan akan meningkatkan kemungkinan seseorang melakukan cyberbullying. Selain itu, seseorang yang pernah menjadi korban atau terkena cyber victimization akan lebih mungkin menjadi pelaku cyberbullying. Namun demikian, dalam penelitian ini, Kontrol Sekolah tidak memiliki pengaruh terhadap perilaku cyberbullying pada remaja SMA di Kota Depok, atau H0 dapat diterima dan H3 ditolak. Dalam penelitian ini, kontrol sekolah meliputi peraturanÂ sekolah terkait cyberbullying dan regulasi penggunaan handphone serta media sosial di sekolah. Beberapa faktor yang membuat kontrol sekolah tidak berpengaruh, antara lain hampir 50% siswa tidak mengetahui bahwa sekolah mereka memiliki peraturan mengenai cyberbullying dan penggunaan media sosial. Selain itu, tidak ada pengawasan dari guru dalam penggunaan media sosial siswa, artinya sekolah belum optimal dalam menegakkan aturan cyberbullying ini.